AN ANALYSIS OF DISCOVERY LEARNING STRATEGY IN ENGLISH LEARNING PROCESS AT EIGHTH GRADE ON SMP NEGERI 2 HILIDUHO IN 2022/2023 - Lase, Krisna Yanti; Telaumbanua, Yasminar Amaerita; Waruwu, Yaredi; Zega, Riswan (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
Discovery Learning Strategy is a strategy used by English teacher in English learning process. Discovery Learning Strategy can increase the students' activeness in English learning process. The purpose of this study is to find out how the implementation of Discovery Learning Strategy in the English learning process and secondly to analyse how students' English learning result in the implementation of Discovery Learning Strategy in English learning process. This research uses a descriptive qualitative approach. The research instruments used were lesson plans, observation sheets, and field notes. The results showed that in the learning process using the Discovery Learning Strategy, the English teacher had used the lesson plan as a guideline in learning. In the lesson plan, there are procedures carried out by the English teacher. The implementation of Discovery Learning Strategy in greeting card learning has been going well, it is proven that when English teacher do the learning process by using Discovery Learning Strategy, the students look active in participating in learning, especially in greeting card material. The implementation of Discovery Learning Strategies in class VIII-B had an impact on the student learning result. From the results of tests conducted by English teacher in the class that the implementation of Discovery Learning Strategies has a positive impact on improving the student learning results. From the test results that had been given many students who answer correctly and reach the MCC.